2013
DOI: 10.1080/13557858.2012.754408
|View full text |Cite
|
Sign up to set email alerts
|

One size fits all? The discursive framing of cultural difference in health professional accounts of providing cancer care to Aboriginal people

Abstract: While none of our participants were dismissive of the idea that cultural identity might matter to Aboriginal people, their reliance upon familiar narratives about what that means for cancer care services has the potential to both symbolically and practically exclude the voices of a group of people who may already feel disenfranchised from the mainstream health care system. Critically unpacking the 'taken for granted' assumptions behind how health care professionals make sense of cultural difference can enrich … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 27 publications
(12 reference statements)
1
25
0
Order By: Relevance
“…Consistent with recent studies (Newman et al . ; Dwyer et al . ), participants in our study explained that providing standard care for all or by treating all patients the same within the limits of the existing system helps to manage the complex needs of a diverse population.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with recent studies (Newman et al . ; Dwyer et al . ), participants in our study explained that providing standard care for all or by treating all patients the same within the limits of the existing system helps to manage the complex needs of a diverse population.…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study in NSW identified several cultural barriers between Aboriginal people and mainstream cancer services that may be subtly contributing to lower usage or acceptability of some cancer treatments. In particular it identified lower cancer literacy for Aboriginal people [31], a feeling of a lack of social inclusion when in hospital settings [32], and the need for health services to openly discuss and address cultural differences in service delivery [33]. …”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular disease is the leading cause of death in Indigenous Australians 9 . Cancer is the second biggest killer: the mortality rate for some cancers is three times higher for Indigenous than for non‐Indigenous Australians 10 . Clinical leaders in these two disease areas have identified the need for culturally safe health care to improve Indigenous health outcomes.…”
mentioning
confidence: 99%
“…Newman and colleagues 10 identified clinician reliance on stereotypical narratives of indigeneity in informing cancer care services. Redressing these taken‐for‐granted assumptions led to culturally engaged and more effective cancer care.…”
mentioning
confidence: 99%